Effects of acute ingestion of caffeinated chewing gum on performance in elite judo athletes - Filip-Stachnik, A.; Krawczyk, R.; Krzysztofik, M.; Rzeszutko-Belzowska, A.; Dornowski, M.; Zajac, A.; Del Coso, J.; Wilk, M. (Journal of the International Society of Sports Nutrition, 2021)
Purpose: Previous investigations have found positive effects of acute ingestion of capsules containing 4-to-9 mg of caffeine per kg of body mass on several aspects of judo performance. However, no previous investigation has tested the effectiveness of caffeinated chewing gum as the form of caffeine administration for judoists. The main goal of this study was to assess the effect of acute ingestion of a caffeinated chewing gum on the results of the special judo fitness test (SJFT). Methods: Nine male elite judo athletes of the Polish national team (23.7 ± 4.4 years, body mass: 73.5 ± 7.4 kg) participated in a randomized, crossover, placebo-controlled and double-blind experiment. Participants were moderate caffeine consumers (3.1 mg/kg/day). Each athlete performed three identical experimental sessions after: (a) ingestion of two non-caffeinated chewing gums (P + P); (b) a caffeinated chewing gum and a placebo chewing gum (C + P; ~2.7 mg/kg); (c) two caffeinated chewing gums (C + C; ~5.4 mg/kg). Each gum was ingested 15 min before performing two Special Judo Fitness Test (SJFT) which were separated by 4 min of combat activity. Results: The total number of throws was not different between P + P, C + P, and C + C (59.66 ± 4.15, 62.22 ± 4.32, 60.22 ± 4.08 throws, respectively; p = 0.41). A two-way repeated measures ANOVA indicated no significant substance × time interaction effect as well as no main effect of caffeine for SJFT performance, SJFT index, blood lactate concentration, heart rate or rating of perceived exertion. Conclusions: The results of the current study indicate that the use of caffeinated chewing gum in a dose up to 5.4 mg/kg of caffeine did not increase performance during repeated SJFTs.